The process of political socialization concept and major theories The process of political socialization concept and major theories - عبدالكریم, م.م. شەهلا محمد عبدالكریم; عبداللە, آ.م.د. عبداللە خورشید عبداللە (Sulaimani Journal for Humanities, 2025)
This study addresses the concept of political socialization, its historical development, and its most important characteristics and stages, along with the major theories that have examined this process. Political socialization is considered one of the fundamental processes that contributes to educating, training, and instilling political ideas, beliefs, and orientations within society. It also plays a role in forming a positive political personality, with the aim of achieving political stability and raising individuals’ awareness of participation in political events and activities, such as voting, protests, and engagement with issues that may pose a threat to society and political authority.Through this process, ideas and beliefs can be transmitted from one generation to another, and future generations can be nurtured to develop love for their homeland and people, thereby strengthening national belonging.
Keywords: Political socialization; socialization